2020
DOI: 10.1097/bpo.0000000000001653
|View full text |Cite
|
Sign up to set email alerts
|

Delays in Obtaining Knee MRI in Pediatric Sports Medicine: Impact of Insurance Type

Abstract: Background: Increased enrollment in government-based insurance plans has been reported. With youth sports injuries on the rise, increased ordering of advanced imaging such as magnetic resonance imaging (MRI) has occurred. This study sought to report on the impact of insurance type on access to and results of knee MRI in pediatric sports medicine patients. Methods: A retrospective review of 178 consecutive pediatric sports medicine clinics was completed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…Numerous studies since then have shown that any of the following may result in delayed treatment among patients with public insurance: limited patient resources; a small number of surgeons accepting public insurance, potentially related to low Medicaid reimbursements; and a lack of appointment times. 6,14,16,24,26 Despite these consistent findings in the literature and changes to health care in the United States, children with public insurance continue to experience disparities in orthopaedic care 20 years later. Kitchen et al 17 recently analyzed the care timeline in 21 of the most common pediatric fractures, noting that delay between injury and referral is the primary reason for the late orthopaedic evaluation experienced by patients with public insurance.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Numerous studies since then have shown that any of the following may result in delayed treatment among patients with public insurance: limited patient resources; a small number of surgeons accepting public insurance, potentially related to low Medicaid reimbursements; and a lack of appointment times. 6,14,16,24,26 Despite these consistent findings in the literature and changes to health care in the United States, children with public insurance continue to experience disparities in orthopaedic care 20 years later. Kitchen et al 17 recently analyzed the care timeline in 21 of the most common pediatric fractures, noting that delay between injury and referral is the primary reason for the late orthopaedic evaluation experienced by patients with public insurance.…”
Section: Discussionmentioning
confidence: 87%
“…Numerous studies since then have shown that any of the following may result in delayed treatment among patients with public insurance: limited patient resources; a small number of surgeons accepting public insurance, potentially related to low Medicaid reimbursements; and a lack of appointment times. 6,14,16,24,26 Despite these consistent findings in the literature and changes to health care in the United States, children with public insurance continue pediatric patients with an ACL tear are more likely to experience prolonged time from injury to presentation and from evaluation to surgery. 9,31 Ultimately, these delays in evaluation and treatment are associated with more severe concomitant meniscal and chondral pathology and inferior clinical outcomes.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The timing to diagnosis via MRI is also impacted for these knee injuries. Beck et al examined 168 patients who underwent knee MRI and found that the time between injury and MRI was significantly longer for government-insured patients (34 days versus 67 days) as was the time between 1st visit and MRI and MRI order and completion [41].…”
Section: Pathology-specific Disparitiesmentioning
confidence: 99%